Pembelian Produk pada R3K Rumah Konveksi: Pengaruh Kualitas Produk dan Promosi - Muzhoffar, Zhaimmul; TeIagawathi, Ni Luh Wayan Sayang (Jurnal Pendidikan Ekonomi Undiksha, 2021)
This study aims to examine the effect of product quaIity and promotion on purchasing decisions. The research design used in this research is causaI quantitative. The subjects in this study were R3K Rumah Confection and the objects in this study were product quaIity, promotion and purchase decisions. The data coIIection method used a questionnaire, which was then anaIyzed using muItipIe Iinear regression anaIysis with the cIassicaI assumption test. The resuIts of this study indicate that (1) there is a positive and significant effect of product quaIity and promotion on purchasing decisions, (2) there is a positive and significant effect of product quaIity on purchasing decisions, and (3) there is a positive and significant effect of promotion on purchasing decisions. purchase.Â